Double-layer speed optimization for reducing fuel consumption with vehicle-to-infrastructure communication. Issue 5 (3rd September 2019) - Xu, Biao; Chen, Xiaolong; Li, Keqiang; Hu, Manjiang; Bian, Yougang; Yu, Qianwen; Wang, Jianqiang
Abstract: Speed profiles affect fuel economy tremendously, especially, when vehicles running on an urban road with numerous signalized intersections. To improve fuel economy, in this study, we propose a double-layer speed optimization method with real-time computation that considers traffic signal information collected via vehicle-to-infrastructure communication and traffic conditions. In the first layer, we use a Dijkstra algorithm to optimize the average eco-speed between adjacent intersections with full-horizon traffic signal information, and in the second layer, we use an optimal control method to plan a real-time speed profile with average speed constraints. We conduct numerous field tests using a test bed and an experimental vehicle platform. The test results demonstrate that by computing optimal solutions in real time, the proposed double-layer speed optimization method has the potential to improve fuel economy and decrease trip time.